2020
DOI: 10.1101/2020.07.10.193979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intermolecular Channels Direct Crystal Orientation in Mineralized Collagen

Abstract: The mineralized collagen fibril is the basic building block of bone, commonly pictured as a parallel array of ultrathin carbonated hydroxyapatite (HAp) platelets distributed throughout the collagen. This orientation is often attributed to an epitaxial relationship between the HAp and collagen molecules inside 2D voids within the fibril. Although recent studies have questioned this model, the structural relationship between the collagen matrix and HAp, and the mechanisms by which collagen directs minera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 75 publications
5
50
1
2
Order By: Relevance
“…In Figure 11, both in the SEDC and OI type IV bone images, black dots that are spanning the whole section, are gold nanoparticles which were used as fiducial markers for the 3D reconstruction. In OI type IV and SEDC bone, collagen fibrils are identifiable in 2D TEM images by the presence of the gap and overlap regions that are repeated along the lengths of the thin slices (Figure 11a projections of 10 added adjacent tomographic xz slices (total slice thickness 7.5 nm) showed that intrafibrillar crystals were randomly oriented in lateral directions, consistent with recent results (Xu et al, 2020) and have no preferred lateral orientation, with an angular distribution having a half-width of about 60 (Figure 12h) for SEDC bone.…”
Section: Characteristic Features Of Collagen Fibrils and Mineralssupporting
confidence: 89%
“…In Figure 11, both in the SEDC and OI type IV bone images, black dots that are spanning the whole section, are gold nanoparticles which were used as fiducial markers for the 3D reconstruction. In OI type IV and SEDC bone, collagen fibrils are identifiable in 2D TEM images by the presence of the gap and overlap regions that are repeated along the lengths of the thin slices (Figure 11a projections of 10 added adjacent tomographic xz slices (total slice thickness 7.5 nm) showed that intrafibrillar crystals were randomly oriented in lateral directions, consistent with recent results (Xu et al, 2020) and have no preferred lateral orientation, with an angular distribution having a half-width of about 60 (Figure 12h) for SEDC bone.…”
Section: Characteristic Features Of Collagen Fibrils and Mineralssupporting
confidence: 89%
“…Apatite crystals follow an asymmetrical, subtly splaying organization pattern inside the continuous collagenous matrix. HA crystals orient along with c-axes of microfibrils in an additional diffraction ring at ~2.8 Å, resulting in beyond recognition and diffractions [57]. These diffractions come from multiple lattice planes.…”
Section: Thementioning
confidence: 99%
“…And it also deduces an angular distribution of ~±20 °in these orientations by tomographic construction of 150 crystals. Other crystal orientations can only grow via pushing the collagen molecules, which presumes that the HA crystal orientations depend on the restraints from collagen, not on the chemical interaction [57]. For extra fibrillar mineralization, the crystals aggregate and densify prenucleation clusters to form the spherical ACP, which is the intermediate product during the nucleation pathway.…”
Section: Thementioning
confidence: 99%
“…[7b, 8] Specifically,o wing to the facet-selective interaction between proteins and inorganic crystals,t he orientation and polymorph of bone nanostructures are delicately regulated with outstanding mechanical functions. [8,9] Except for that, nanostructures assembled with facet selectivity have also been demonstrated to display fantastic facet-dependent optical properties and enzymatic properties, enabling huge advantages in fields including photonics, [10] metabolism, [11] and catalysis. [12] Therefore,b ioinspired construction of facet-selective nanostructures can not only help to reveal the growth mechanisms of biominerals with abetter understanding of the structure-function relationship,but also offer extensive opportunities for the design and applications of multifunctional advanced materials.…”
Section: Introductionmentioning
confidence: 99%